213k views
5 votes
(4x-3)^2-(2x+5)^2=0 tìm x

User Madaline
by
5.4k points

1 Answer

1 vote

Hi

Your question would be better with " Could you help me please ? " at the end. Quite sure your mum told you that some time in the past.

I will show you how to solve but you will do the calculus. Math is all about rules, methods and training. If you dont practice, you will never progress.

rule : you must know by heart your remarkable identities.

Here we have : ( 4x-3)² - (2x+5)² = 0

It 's of the form A² -B² = ( A+B) ( A-B)

here A is : 4x-3 and B is 2x+5

Now let's apply rule : ( 4x-3)² - (2x+5)² = ( (4x-3) +( 2x+5) ) ( (4x-3) - (2x+5)

= ( 4x-3 +2x+5 ) ( 4x-3 -2x-5 )

= ( 6x +2) ( 2x-8)

so : ( 4x-3)² - (2x+5)² = ( 6x +2) ( 2x-8)

so ( 4x-3)² - (2x+5)² = 0 means : ( 6x +2) ( 2x-8) = 0

Rule A*B = 0 if A = 0 or B = 0

A is 6x+2 and B = 2x-8

So I let you now work :

You have to solve : 6x+2 = 0

and 2x-8 = 0

Solutions of this two calculus will be the solutions of ( 4x-3)² - (2x+5)² = 0

Have fun !

User Dmitry Teplyakov
by
5.8k points